Fracture-induced amorphization of polycrystalline SiO(2) stishovite: a potential platform for toughening in ceramics - Nishiyama, Norimasa (Nature Publishing Group, 2014)
Silicon dioxide has eight stable crystalline phases at conditions of the Earth's rocky parts. Many metastable phases including amorphous phases have been known, which indicates the presence of large kinetic barriers. As a consequence, some crystalline silica phases transform to amorphous phases by bypassing the liquid via two different pathways. Here we show a new pathway, a fracture-induced amorphization of stishovite that is a high-pressure polymorph. The amorphization accompanies a huge volume expansion of ~100% and occurs in a thin layer whose thickness from the fracture surface is several tens of nanometers. Amorphous silica materials that look like strings or worms were observed on the fracture surfaces. The amount of amorphous silica near the fracture surfaces is positively correlated with indentation fracture toughness. This result indicates that the fracture-induced amorphization causes toughening of stishovite polycrystals. The fracture-induced solid-state amorphization may provide a potential platform for toughening in ceramics.